Iron deficiency anaemia to laparotomy - A hair-raising tale - Holly Campbell; Christopher Maguire; Roy Kimble (Elsevier, 2018)
Abdominal pain is among the most common presenting complaints observed in paediatric emergency departments. One uncommon cause of this presentation in the paediatric population is a trichobezoar. Within the broader literature, this pathology has almost exclusively been observed in teenagers with a concomitant psychiatric diagnosis. We present a rare case of an alternate aetiology - a child in whom iron deficiency anaemia (IDA) precipitated pica behaviours that subsequently led to the formation of a trichobezoar requiring surgical removal. Although rare, this case highlights the importance of considering iron deficiency anaemia induced pica as a precipitant of trichobezoar in the surgical work-up of children presenting to a health facility with abdominal pain. Keywords: Pica, Trichobezoar, Iron deficiency anaemia